The Impact of the Staphylococcus aureus Virulome on Infection in a Developing Country: A Cohort Study - Lebughe, Marthe; Phaku, Patrick; Niemann, Silke; Mumba, Dieudonné; Peters, Georg; Muyembe-Tamfum, Jean-Jacques; Mellmann, Alexander; Strauß, Lena; Schaumburg, Frieder (Frontiers in Microbiology, 2017)
We performed a cohort study to analyze the virulome of Staphylococcus aureus from the Democratic Republic of Congo using whole genome sequencing (WGS) and to assess its impact on the course of S. aureus infections. Community-associated S. aureus from nasal colonization (n=100) and infection (n=86) were prospectively collected. Phenotypic susceptibility testing and WGS was done for each isolate. WGS data were used to screen for 79 different virulence factors and for genotyping purposes (spa typing, multilocus sequence typing). The majority of the 79 virulence factors were equally distributed among isolates from colonization and infection. Panton-Valentine leukocidin (PVL) and the non-truncated hemolysin β were associated with skin and soft tissue infection (SSTI) and recurrence of disease but did not influence the course of infection (i.e. mortality, surgical intervention). For the first time, we show that not only PVL but also hemolysin β could contribute to the development of SSTI in PVL-endemic areas such as Africa.